SEARCH FOR ISOSINGLET NEUTRAL HEAVY-LEPTONS IN Z0 DECAYS - Adriani, O; Aguilarbenitez, M; Ahlen, S; Alcaraz, J; Aloisio, A; Alverson, G; Alviggi, M; Ambrosi, G; An, Q; Anderhub, H; Anderson, A; Andreev, V; et al. (1992)
We search for neutral heavy leptons that are isosinglets under the standard SU (2)L gauge group. Such neutral heavy leptons are expected in many extensions of the standard model. Three types of heavy leptons Ne, Nμ, Nτ associated with the three neutrino types ve, vμ, vτ have been directly searched for and no evidence for a signal has been found. We set the limit Br(NSu0 → vℓNℓ) < 3 x 10-5 at the 95% CL for mass range from 3 GeV up to Mz. © 1992.